Redesain Pasar Baru Cikarang Dengan Konsep Industrial Architecture - Retno Fitri Astuti; Slamet Riyadi (Prosiding Sains dan Teknologi, 2022)
The market is one aspect in driving the economy and as a means to meet the needs od the sommunity. Pasar Baru Cikarang is one of the main market in Bekasi Regency for the Cikarang area. Pasar Baru Cikarang has historically been an impressive market which underwent construction and renovation in 1992, conmpleted construction in 1994 and started operating in 1995. Looting event that occurred throughout into street vendors. As a result of traders turning to street vendors, market conditions are increasingly looking shabby and untidy. This slum condition makes the primary area which is the storefront of Bekasi Regency, especially Cikarang, which is an ASEAN Industrial City look less good. As an industrial city, it is necessary to have an architectural object that becomes an icon of an industrial city by emphasizing the concept of industrial architecture. It has a minimal concept of final finishing in buildings as its special feature, so its very suitable to be applied to market buildings. By applying it to the Pasar Baru Cikarang, it is hoped that it can lift the imagr of the market which is starting to dim and can also become of the icon of the Industial City. Keywords: Redesign, Cikarang New Market, Industrial Architecture, Industrial City